2020
DOI: 10.1007/s10072-020-04754-2
|View full text |Cite
|
Sign up to set email alerts
|

The stroke mothership model survived during COVID-19 era: an observational single-center study in Emilia-Romagna, Italy

Abstract: Introduction A reduction of the hospitalization and reperfusion treatments was reported during COVID-19 pandemic. However, high variability in results emerged, potentially due to logistic paradigms adopted. Here, we analyze stroke code admissions, hospitalizations, and stroke belt performance for ischemic stroke patients in the metropolitan Bologna region, comparing temporal trends between 2019 and 2020 to define the impact of COVID-19 on the stroke network. Methods This retrospective observational study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 12 publications
3
33
0
Order By: Relevance
“…There was a transient increase in admissions before the 'second wave' of the pandemic in April-May 2020 (Figure 3). Moreover, similar to prior studies, we noticed a significant drop in patients with mild strokes (NIHSS 1-5), 9,30,35 but there was no difference in last known well to hospital arrival or the number of cases treated with thrombolysis and thrombectomy in our cohort. 8,19 A number of reasons have been postulated to explain the reduced stroke admissions witnessed during the ongoing pandemic.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There was a transient increase in admissions before the 'second wave' of the pandemic in April-May 2020 (Figure 3). Moreover, similar to prior studies, we noticed a significant drop in patients with mild strokes (NIHSS 1-5), 9,30,35 but there was no difference in last known well to hospital arrival or the number of cases treated with thrombolysis and thrombectomy in our cohort. 8,19 A number of reasons have been postulated to explain the reduced stroke admissions witnessed during the ongoing pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 52 studies reporting the impact of the COVID‐19 pandemic on stroke admissions were identified for qualitative synthesis. A total of 32,640 stroke admissions from 29 studies 6‐34 were included in the meta‐analysis (Figure 1) (Supplementary Table S1) based on a similar time frame of the study period and comparison period, of which ratios were derived, depending on each criterion data availability. Compared to the prepandemic period, the mean ratio of stroke admissions during the pandemic was 70.78% [95% CI: (65.02%, 76.54%)] (Figure 2) and the mean ratio of ICH cases was 83.10% [95% CI: (71.01%, 95.17%)] (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Similar admission trends were observed in the UK where there was also an increase in the average severity of cases arriving in hospital [ 9 ]. An analysis of data in a secondary phase of the pandemic in tertiary care unit in Italy showed that the most serious strokes had hospital access rates comparable to previous years and the contraction was mainly in the milder forms [ 10 ]. Policies minimizing provider-patient interactions as well as personal reticence to come to the ED during the pandemic might have participated in such contraction, which has prompted international societies to speak up to maintain efficient stroke pathways.…”
mentioning
confidence: 99%
“…Keeping a pre-hospital organization around a tertiary referral center capable of thrombectomy is essential for holding the quality of care in stroke to the highest standards [ 15 , 16 ] . Recent meta-analysis have favoured the “Directly to mothership” model over the “Drip and ship” one [ 17 , 18 ] , and a study done in another Italian hospital (Ospedale Maggiore, Bologna) during the SARS-CoV-2 pandemic also shared this view [ 19 ] . However, in the specific setting of NCGH, the sudden shut down of SC and redirection of stroke patients directly to the ER-NCGH, already overwhelmed with the surge of the SARS-CoV-2 infection, may not have worked in its favour.…”
Section: Discussionmentioning
confidence: 99%
“…One could argue that NCGH would not benefit as much with a change in the pre-hospital organization, or that the results would've been different if a “Mothership” model was already in place. In the case of our fellow colleagues from Ospedale Maggiore, Bologna, the Mothership model had been established 2 years prior to the pandemic [ 19 ] . Lastly, a small percentage of data was missing, namely CT scans performed in other hospitals, which could not be reviewed for the purpose of this study.…”
Section: Discussionmentioning
confidence: 99%